Kepemimpinan Kepala Madrasah Dalam Mengembangkan Lembaga Pendidikan Islam - Ahmad Fauzi (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2017)
Leadership becomes the main determinant of the process of the birth of the dynamics of an education and the effectiveness of leadership. It is mutlaq needed to build and encourage the achievement of the quality of education. Effective leadership is the realization of a blend of talent and experience in changing circumstances as it takes place through the interaction between fellow human beings. Because the findings in the field to interpret the success in leadership related 3 indicators are: (1) Quality Leadership of Madrasah Principals in the Development of Islamic Education Institutions, (2) Leadership Efforts Heads of Madrasahs in Development of Islamic Education Institutions, (3) Supporting Factors And Inhibitors Leadership Madrasahs in the Development of Islamic Education Institutions.